Taxation and Innovation in the Twentieth Century. Issue 1 (4th June 2021) - Akcigit, Ufuk; Grigsby, John; Nicholas, Tom; Stantcheva, Stefanie
Abstract: This article studies the effect of corporate and personal taxes on innovation in the United States over the twentieth century. We build a panel of the universe of inventors who patented since 1920, and a historical state-level corporate tax database with corporate tax rates and tax base information, which we link to existing data on state-level personal income taxes and other economic outcomes. Our analysis focuses on the effect of personal and corporate income taxes on individual inventors (the micro level) and on states (the macro level), considering the quantity and quality of innovation, its location, and the share produced by the corporate rather than the noncorporate sector. We propose several identification strategies, all of which yield consistent results. We find that higher taxes negatively affect the quantity and the location of innovation, but not average innovation quality. The state-level elasticities to taxes are large and consistent with the aggregation of the individual-level responses of innovation produced and cross-state mobility. Corporate taxes tend to especially affect corporate inventors' innovation production and cross-state mobility. Personal income taxes significantly affect the quantity of innovation overall and the mobility of inventors.